The Environmental Footprint of Foreign Investment in Bulgaria - Huseynli, Bahman; Kandemir Comoglu, Gözde; Huseynli, Nigar (International Journal of Energy Economics and Policy, 2025)
Foreign direct investments, a crucial strategy for attracting foreign capital, include certain downsides alongside their benefits. An illustration of this is the rise in carbon dioxide (CO2) emissions discharged into the environment. The aim of this study is to investigate the relationship between CO2 emissions in Bulgaria and foreign investments. The study is quantitative research, and the Granger method was used. The study was based on World Bank data for the years 1998-2022. The study’s limitation to 24 years of data stems from the unavailability of data for more years. Based on the findings of the study, there was no correlation found between CO2 emissions in Bulgaria and investments from other countries. It is possible that foreign investments will have a greater impact on the environment over the long term, even if this impact is not visible during the period of investment. Using the Granger method, it has been empirically proven that there is no causal relationship between CO2 emissions and foreign direct investments in Bulgaria in the period 1998-2022. Policymakers have the ability to design policies that encourage foreign investments in environmentally friendly and sustainable technology, as well as laws that assist in directing future investments toward projects that are ecologically favorable.